Nancy Drew and the Clue Crew : Sleepover Sleuths - Book 1 - Keene, Carolyn; Pamintuan, Macky (New York : Aladdin Paperbacks, 2008)
When eight-year-old Nancy is invited to a sleepover party with a dolls theme, the host's doll goes missing and Nancy tries to solve her first case.
Reprint. Originally published: 2006.
Keywords: Sleepovers -- Fiction; Dolls -- Fiction; Mystery fiction